2020
DOI: 10.1589/jpts.32.534
|View full text |Cite
|
Sign up to set email alerts
|

Optimal foot-position of caregiver based on muscle activity of lower back and lower limb while providing sit-to-stand support

Abstract: [Purpose] In caregivers, low load posture is necessary to prevent lower back pain during patient handling activities such as sit-to-stand support. This study focused on the foot-position of caregivers as an adjustable and useful parameter. A wide stance decreases the stress on the lumbar vertebra. However, this foot-position increases loading of the spinae erector muscles. The aim of this study was to investigate the relationship of anterior-posterior and lateral-medial distances between feet and activity of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Such a type of patient handling causes lower back pain among caregivers as a patient is frequently repositioned on a bed [15]. As explained above, arm movements and foot positions are important factors for patient handling [11][12][13]. Thus, this study proposes the recognition method for various foot positions and arm movements of caregivers using a postural recognition method during postural change for a patient on a bed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a type of patient handling causes lower back pain among caregivers as a patient is frequently repositioned on a bed [15]. As explained above, arm movements and foot positions are important factors for patient handling [11][12][13]. Thus, this study proposes the recognition method for various foot positions and arm movements of caregivers using a postural recognition method during postural change for a patient on a bed.…”
Section: Introductionmentioning
confidence: 99%
“…However, this system cannot suggest caregiver ways to adjust to an appropriate posture because the system measures only the trunk angle. Several factors, such as the foot position and arm movement, are useful to achieve suitable postures to prevent lower back pain during patient handling [11][12][13]. Therefore, a simple and wearable system that monitors the trunk angle, foot position, and arm movement is being develop [14].…”
Section: Introductionmentioning
confidence: 99%
“…Posture adjustment based on ergonomics has been found to be effective for reducing lumbar load during manual lifting [ 4 ]. Trunk angle and foot position have been considered important posture parameters for reducing the lumbar load during manual lifting [ 5 , 6 , 7 , 8 ]. Hoogendoorn et al reported that trunk flexion and rotation are risk factors for the development of LBP [ 5 ], whereas Delisle et al found that strategic foot placement might improve lumbar load during manual handling [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hoogendoorn et al reported that trunk flexion and rotation are risk factors for the development of LBP [ 5 ], whereas Delisle et al found that strategic foot placement might improve lumbar load during manual handling [ 6 , 7 ]. Our previous studies suggest that the adjustment of the quantitative foot position could reduce the lumbar load during assistive motion for sit-to-stand [ 8 , 9 ]. A previous investigation using computational musculoskeletal simulation revealed that foot position with long anteroposterior foot distance can reduce the compression stress in the L4–L5 joint [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation